2022
DOI: 10.3390/cancers14225580
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Cancer: Current Multimodality Treatment Concepts and Future Directions

Abstract: Gallbladder cancer (GBC) is the most common primary tumor site of biliary tract cancer (BTC), accounting for 0.6% of newly diagnosed cancers and 0.9% of cancer-related deaths. Risk factors, including female sex, age, ethnic background, and chronic inflammation of the gallbladder, have been identified. Surgery is the only curative option for early-stage GBC, but only 10% of patients are primary eligible for curative treatment. After neoadjuvant treatment, up to one-third of locally advanced GBC patients could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 158 publications
0
17
0
1
Order By: Relevance
“…For locally advanced gallbladder cancer, neoadjuvant chemotherapy could transform primary non-resectable patients into eligible patients for resection. However, the current evidence does not cover cases of gallbladder cancer within a duplicated gallbladder [ 17 ]. More future studies and data collection would be useful to determine the most appropriate management of this rare presentation.…”
Section: Discussionmentioning
confidence: 99%
“…For locally advanced gallbladder cancer, neoadjuvant chemotherapy could transform primary non-resectable patients into eligible patients for resection. However, the current evidence does not cover cases of gallbladder cancer within a duplicated gallbladder [ 17 ]. More future studies and data collection would be useful to determine the most appropriate management of this rare presentation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Multimodal treatment has been increasingly considered as an important treatment strategy for patients diagnosed with BTC. 26,27 Despite this benefit, adjuvant treatment for BTC is known to be underutilized. 28,29 For example, Kemp Bohan et al revealed that among patients with resected pathologic stage I-III GBC, only 17.5% of individuals received adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal treatment has been increasingly considered as an important treatment strategy for patients diagnosed with BTC 26,27 . Despite this benefit, adjuvant treatment for BTC is known to be underutilized 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…GBC is early‐stage asymptomatic and lacks early effective screening methods. The vast majority of patients have already developed local invasion and distant metastasis at the time of diagnosis, thus missing the chance of radical resection, and even patients who undergo radical resection often relapse within 1 year 4 . Given the highly aggressive biological behavior and poor prognosis of GBC, it is critical to investigate the mechanisms underlying its progression and metastasis and identify potential therapeutic targets to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%